Examining the Impact of Moral Intelligence Training on the Social Skills Components of Young Female Elementary School Students - Khadir, Raziyeh (Iranian Journal of Neurodevelopmental Disorders, 2025)
Purpose: This study aimed to investigate the effect of moral intelligence training on the social skills components of young female elementary school students in Bandar Abbas City during the 2020–2021 academic year. Methods and Materials: The research employed a quasi-experimental design with a pretest–posttest and control group. Two elementary schools were randomly selected in Bandar Abbas City to form the sample group. All students from these schools completed the Gresham and Elliott Social Skills Rating System (SSRS) questionnaire. From each school, 15 students with the lowest scores on the questionnaire were selected; one school was designated as the experimental group and the other as the control group. The experimental group received moral intelligence training across 11 sessions, each lasting two hours per week. After the intervention, both groups completed the social skills questionnaire again. Data were analyzed using multivariate analysis of covariance (MANCOVA). Findings: The results demonstrated a significant improvement in the components of social skills—including cooperation, assertiveness, and self-control—among students in the experimental group compared to those in the control group (p < .05). Conclusion: These findings indicate that moral intelligence training is effective in enhancing self-control and other social skill components in children.